A critical analysis of DEA applications to seaport economic efficiency measurement - Panayides, Photis; Maxoulis, Christos N.; Wang, Teng Fei; Ng, Koi Yu Adolf (My University, 2009)
The significant increase in the adoption of Data Envelopment Analysis (DEA) for seaport efficiency measurement renders a literature synthesis and critical analysis of the application of the technique relevant and worthwhile. This paper provides a thorough review and critical analysis of the major studies undertaken to date, and highlights some problems and limitations in the application of the technique in the seaport context particularly in the specification of parameters, the sampling domain and the type of DEA to be applied. The paper informs the decision process as to the merits and limitations of DEA approaches for seaport efficiency measurement and makes a contribution towards methodological improvement by considering variations not yet applied to the port sector
Keywords: Transportation; Data envelopment analysis; Harbors